2022
DOI: 10.1167/tvst.11.2.9
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Oxygen Delivery and Extraction in Ophthalmologically Healthy Subjects With Different Blood Pressure Status

Abstract: Purpose To compare retinal oxygen delivery (DO 2 ) and oxygen extraction (VO 2 ) in ophthalmologically healthy subjects with different blood pressure (BP) status. Methods In this case-control study, we prospectively included 93 eyes of 93 subjects (aged 50–65 years) from a Dutch cohort ( n = 167,000) and allocated them to four groups (low BP, normal BP [controls], treated arterial hypertens… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…We found that localized RNFL defects were associated with central obesity. Previous studies also reported that obesity (high BMI) was associated with a thinner RNFL ( 4 - 6 ). In a recent study, a higher BMI was associated with reduced retinal oxygen delivery and extraction in healthy subjects.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…We found that localized RNFL defects were associated with central obesity. Previous studies also reported that obesity (high BMI) was associated with a thinner RNFL ( 4 - 6 ). In a recent study, a higher BMI was associated with reduced retinal oxygen delivery and extraction in healthy subjects.…”
Section: Discussionmentioning
confidence: 74%
“…Localized RNFL defects have been associated with certain components of metabolic syndrome in previous studies, including obesity ( 4 - 6 ), cardiovascular risk factors ( 7 ), hypertension ( 7 - 10 ), and albuminuria in patients with type 2 diabetes ( 11 ). Metabolic syndrome is a growing epidemic estimated at 1.4 billion worldwide and rising every year ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Oxygen supply to the inner retina is provided solely by the retinal circulation, whereas oxygen supply to the outer retina is provided primarily by diffusion from the choroidal circulation, with negligible supply from the retinal circulation [ 21 ]. Through autoregulatory mechanisms and vessel wall remodeling, the oxygen volume delivered to the outer retinal tissues can be controlled to some extent by the extraction of oxygen from the retinal circulation.…”
Section: Discussionmentioning
confidence: 99%
“…The exact criteria, rationale, and power specifications of the recruitment process have been described extensively in our recent studies on the same population. 26 , 27 In short, the subjects included were required to fall into one of four predefined groups: low BP, normal BP, treated high BP, and untreated high BP. Subjects in the low BP group were invited based on documented recordings of systolic BP (SBP) and diastolic BP (DBP) that were below the respective 10th percentile of the population on two or more separate occasions.…”
Section: Methodsmentioning
confidence: 99%